2011
DOI: 10.1200/jco.2009.27.8911
|View full text |Cite
|
Sign up to set email alerts
|

Topotecan Weekly Versus Conventional 5-Day Schedule in Patients With Platinum-Resistant Ovarian Cancer: A Randomized Multicenter Phase II Trial of the North-Eastern German Society of Gynecological Oncology Ovarian Cancer Study Group

Abstract: With regard to effectiveness in terms of response and PFS, Tc remains the standard of care in patients with platinum-resistant recurrent ovarian cancer. However, comparable OS rates and a favorable toxicity profile make Tw another viable treatment option in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 30 publications
5
57
0
2
Order By: Relevance
“…Topotecan, typically given weekly, seemed less active than weekly paclitaxel, with intermediate results for PLD. This observation is aligned with data suggesting suboptimal efficacy of weekly topotecan, 3 whereas weekly paclitaxel induces high ORRs but disappointing PFS. [4][5][6] However, median OS with chemotherapy alone was similar between cohorts and consistent with historical data.…”
Section: Journal Of Clinical Oncology C O R R E S P O N D E N C Esupporting
confidence: 65%
“…Topotecan, typically given weekly, seemed less active than weekly paclitaxel, with intermediate results for PLD. This observation is aligned with data suggesting suboptimal efficacy of weekly topotecan, 3 whereas weekly paclitaxel induces high ORRs but disappointing PFS. [4][5][6] However, median OS with chemotherapy alone was similar between cohorts and consistent with historical data.…”
Section: Journal Of Clinical Oncology C O R R E S P O N D E N C Esupporting
confidence: 65%
“…Topotecan has also been evaluated in randomised controlled trials (RCTs) at an i.v. dose of 4.0 mg/m 2 weekly, 23 and as an oral treatment (dose of 2.3 mg/m 2 /day). 24 A dose for oral administration of topotecan has not been recommended for ovarian cancer.…”
Section: Topotecanmentioning
confidence: 99%
“…For example, based on CA125 level alone, a patient could be categorised as PPS at baseline but as FPS 4 months later with radiological confirmation. Of the trials identified, seven RCTs 23,28,29,31,48,62,68 reported that patients with only CA125 level as an indicator of recurrent disease were enrolled. In trials in patients with platinum-sensitive disease, there was considerable variation across the trials in the proportion of patients with non-measurable disease at baseline, ranging from 8.5% to 38.2%.…”
Section: Comparability Of Baseline Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, reduced dosing is widely used in standard clinical practice (e.g., 1.25 mg/m 2 ), which confers decreased toxicity and similar outcome [51]. In addition, similar effectiveness with significantly lower hematologic toxicity has been observed in several studies when topotecan is administered on a weekly schedule [52]. Based on this evidence, a conventional (1.25 mg/m 2 on days 1-5 of a 3 week schedule) and an alternative (4.0 mg/m 2 on days 1, 8 and 15 of a 4 week cycle) schedule of topotecan administration were selected for FORWARD I.…”
Section: Background and Rationalementioning
confidence: 85%